Epimutation and Cancer: Carcinogenesis Viewed as Error-Prone Inheritance of Epigenetic Information - Riley, Patrick A. (J Oncol, 2018)
The epimutation concept, that is, malignancy is a result of deranged patterns of gene expression due to defective epigenetic control, proposes that in the majority of adult cancers the primary (initiating) lesion adversely affects the mechanism of vertical transmission of the epigenetic pattern existing in the stem cells of differentiated tissue. Such an error-prone mechanism will result in deviant gene expression capable of accumulation at each mitosis of the affected stem cell clone. It is argued that a proportion of these proliferation products will express combinations of genes which endow them with malignant properties, such as the ability to transgress tissue boundaries and migrate to distant locations. Since the likelihood of this occurrence is dependent on the proliferation of cells manifesting the defective epigenetic transmission, the theory predicts that cancer incidence will be strongly influenced by factors regulating the turnover rate of the stem cells of the tissue in question. Evidence relating to this stipulation is examined. In addition, it would be anticipated on the basis of the selection of genes involved that the susceptibility to malignant transformation will vary according to the tissue of origin and this is also discussed.